Adenosine stress myocardial perfusion imaging and myocardial work in evaluating INOCA - Xuemei Zhang; Shuixiu Dou; Feifei Zhang; Ping Lou; Jing Jin; Ying Zhao; Xin Zhao; Fengsheng Li; Yuhan Li (Scientific Reports)
Abstract To assess myocardial functional abnormalities in ischemia with non-obstructive coronary arteries (INOCA) using adenosine stress myocardial contrast echocardiography (AS-MCE) combined with Myocardial Work (MW). 208 patients who underwent coronary angiography (CAG) or coronary computed tomography angiography (CCTA) due to chest pain at Shaanxi Provincial People's Hospital from January 2022 to April 2025 were selected. Among them, 62 patients with negative results from CAG or CCTA and positive results from AS-MCE were classified as the INOCA group, and 48 normal patients were classified as the control group. Conventional parameters were measured by two-dimensional ultrasound. The left ventricular global longitudinal strain (GLS) and MW parameters were obtained through the EchoPAC (v203) workstation. QLab (v10.8) was used to analyze AS-MCE images at rest and under stress in all subjects to obtain myocardial perfusion parameters: peak signal intensity (A-value), Perfusion intensity (β-value), and A × β -value (reflecting myocardial blood volume). The differences in these parameters between the two groups were compared. Under both resting and stress conditions, the β values of patients in the INOCA group were significantly different from those in the control group, and the CFR in the INOCA group was significantly different from that in the control group (P < 0.05, Table 2). AS-MCE effectively identifies microcirculatory dysfunction in INOCA, demonstrating superior diagnostic utility over MW for non-obstructive ischemia.